The roles of MHC class II genes and post-translational modification in celiac disease - Sollid, Ludvig M. (Immunogenetics (New York), 2017)
Our increasing understanding of the etiology of celiac disease, previously considered a simple food hypersensitivity disorder caused by an immune response to cereal gluten proteins, challenges established concepts of autoimmunity. HLA is a chief genetic determinant, and certain HLA-DQ allotypes predispose to the disease by presenting posttranslationally modified (deamidated) gluten peptides to CD4 + T cells. The deamidation of gluten peptides is mediated by transglutaminase 2. Strikingly, celiac disease patients generate highly disease-specific autoantibodies to the transglutaminase 2 enzyme. The dual role of transglutaminase 2 in celiac disease is hardly coincidental. This paper reviews the genetic mapping and involvement of MHC class II genes in disease pathogenesis, and discusses the evidence that MHC class II genes, via the involvement of transglutaminase 2, influence the generation of celiac disease-specific autoantibodies.